2011
DOI: 10.1371/journal.pone.0026120
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Related Protein 1 Clusters with Ribosomes and Messenger RNAs at a Subset of Dendritic Spines in the Mouse Hippocampus

Abstract: The formation and storage of memories in neuronal networks relies on new protein synthesis, which can occur locally at synapses using translational machinery present in dendrites and at spines. These new proteins support long-lasting changes in synapse strength and size in response to high levels of synaptic activity. To ensure that proteins are made at the appropriate time and location to enable these synaptic changes, messenger RNA (mRNA) translation is tightly controlled by dendritic RNA-binding proteins. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 67 publications
(97 reference statements)
5
34
1
Order By: Relevance
“…Furthermore, histological examination confirmed the presence of recombinant GFP-FXR1P in the cell body and MAP2-positive dendrites of infected cortical neurons (Fig. 5C), thus confirming that the subcellular distribution of GFP-FXR1P corresponds to that of endogenous FXR1P (41). Finally, overexpression of GFP-FXR1P in prelymbic prefrontal cortex neurons replicated the behavioral effects of GSK3β deletion and VAL 10 treatment in the DLET (Fig.…”
Section: Fxr1p Overexpression Replicates Behavioral Effects Of Valprosupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, histological examination confirmed the presence of recombinant GFP-FXR1P in the cell body and MAP2-positive dendrites of infected cortical neurons (Fig. 5C), thus confirming that the subcellular distribution of GFP-FXR1P corresponds to that of endogenous FXR1P (41). Finally, overexpression of GFP-FXR1P in prelymbic prefrontal cortex neurons replicated the behavioral effects of GSK3β deletion and VAL 10 treatment in the DLET (Fig.…”
Section: Fxr1p Overexpression Replicates Behavioral Effects Of Valprosupporting
confidence: 67%
“…A study of hippocampal neurons has shown an association of FXR1P with neuronal polyribosomes in dendritic clusters (41). Furthermore, FXR1P has been recently identified as a negative regulator for the translation of the ionotopic-glutamate AMPA receptor subunit GluA2.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP is an RNA-binding protein that is enriched in neurons, particularly in the cell body, dendrites and postsynaptic spines (14,28,53,54). Dendritic spines, small protrusions along neuronal dendrites, are sites of excitatory synaptic input, which contain receptors and signaling molecules that are essential for synaptic neurotransmission (55).…”
Section: Dendritic Spine Morphology and Neurotransmissionmentioning
confidence: 99%
“…While FXR1P can regulate protein synthesis in non-neuronal cells (Garnon et al, 2005; Vasudevan and Steitz, 2007), its role in mRNA translation and synaptic plasticity in neurons is unknown, largely related to the fact that complete loss of FXR1P in mice results in perinatal lethality (Mientjes et al, 2004). Our recent discovery that FXR1P co-localizes with translation machinery in dendrites and near a subset of dendritic spines (Cook et al, 2011) prompted us to investigate its function in brain development, plasticity and synaptic protein expression and to compare its role to FXR2P and FMRP.…”
Section: Introductionmentioning
confidence: 99%